Impacts of urbanization on the ichthyofauna of streams in a metropolitan region of the state of São Paulo - Barbosa, Bianca Caroline [UNESP]; Paiola, Isabel [UNESP]; Marques-Frisoni, Wellington Junio [UNESP]; Okubo, Vitor Kenzo Niskirara [UNESP]; Shimizu-Alves, Yullia Kaory [UNESP]; Siqueira-Cesar, Poliana [UNESP]; Casatti, Lilian [UNESP] (My University, 2025)
Urbanization causes significant transformations in stream environments, modifying the structure of communities, eliminating sensitive species and favoring tolerant and non-native species. This study characterized the ichthyofauna of urban streams in the metropolitan region of northwestern São Paulo state. Additionally, the species composition was compared with previous records obtained from the same region. The research was conducted in seven urban streams in São José do Rio Preto and Bady Bassitt, SP. The ichthyofauna was sampled in 80-meter stretches, together with the Physical Habitat Index (PHI) and the physicochemical characteristics of the water. Five streams were classified as poor and two as regular according to the PHI. Ten species belonging to four orders and four families were collected, totaling 2,305 individuals. Poecilia reticulata was dominant in frequency and abundance.The current species richness was significantly lower compared to historical records. Diet analysis also revealed the presence of only two trophic guilds, detritivorous and insectivorous, with a predominance of Chironomidae larvae. The study identified that urbanization negatively impacts the ichthyofauna of northwestern São Paulo, reducing species richness and diversity, favoring the dominance of a non-native species, and the predominance of detritus and Chironomidae larvae in diets. The results highlighted the relationship between the physical quality of the environment and the composition of ichthyofauna, demonstrating that more heterogeneous environmental conditions enable greater species diversity.
Impactos da urbanização na ictiofauna de riachos em uma região metropolitana do estado de São Paulo
Keywords: Aquatic ecosystems; Habitat integrity; Poecilia reticulata